Pengaruh Gerakan Senam Chair Exercise Bagi Manula Untuk Mencegah Penyakit Diabetes Mellitus (DM) - hendi imam fadoli (Journal of Sport Science and Education, 2018)
The purpose of Elderly Gymnastics movement is to provide movement activity in the elderly through gymnastics activities reserved specifically for the elderly. To improve the quality of life through the activity of motion is the activity of motion using a chair with low pressure (Chair Exercise). This elderly gymnastics movement as one effort to prevent dangerous diseases that often occur in elderly is Diabetes Mellitus disease. A special target is the improvement of the quality of life through a health standpoint in the elderly, so that the elderly can perform daily activities independently. Health test is done in knowing the benefits of elderly gymnastic movement by performing a simple health check on the elderly, which tests blood glucose levels by using a tool Glucometer.